2018
DOI: 10.1101/489690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudozyma saprotrophic yeasts have retained a large effector arsenal, including functional Pep1 orthologs

Abstract: SummaryThe basidiomycete smut fungi are predominantly plant parasitic, causing severe losses in some crops. Most species feature a saprotrophic haploid yeast stage, and several smut fungi are only known from this stage, with some isolated from habitats without suitable hosts, e.g. from Antarctica. Thus, these species are generally believed to be apathogenic, but recent findings that some of these might have a plant pathogenic sexual counterpart, casts doubts on the validity of this hypothesis. Here, four Pseud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Out of 56 sequences of functionally characterized proteins, only six putative orthologous genes were identified by a tBLASTn search (at least 60% coverage and > 20% identity). These genes included (1) Clp1 required for the proliferation of dikaryotic filaments in planta (Scherer et al 2006 ); (2) defense-suppressing virulence effector Pep1 (Doehlemann et al 2009 ; Hemetsberger et al 2012 , 2015 ; Sharma et al 2018 ); (3) Pep4 involved in dimorphism and pathogenesis (Soberanes-Gutiérrez et al 2015 ); (4) precursor of the peptide conferring surface hydrophobicity to hyphae Rep1 (Wösten et al 1996 ; Müller et al 2008 ; Teertstra et al 2009 ); (5) peroxisomal sterol carrier protein Scp2 (Krombach et al 2018 ); and (6) high-affinity sucrose transporter required for virulence Srt1 (Wahl et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 56 sequences of functionally characterized proteins, only six putative orthologous genes were identified by a tBLASTn search (at least 60% coverage and > 20% identity). These genes included (1) Clp1 required for the proliferation of dikaryotic filaments in planta (Scherer et al 2006 ); (2) defense-suppressing virulence effector Pep1 (Doehlemann et al 2009 ; Hemetsberger et al 2012 , 2015 ; Sharma et al 2018 ); (3) Pep4 involved in dimorphism and pathogenesis (Soberanes-Gutiérrez et al 2015 ); (4) precursor of the peptide conferring surface hydrophobicity to hyphae Rep1 (Wösten et al 1996 ; Müller et al 2008 ; Teertstra et al 2009 ); (5) peroxisomal sterol carrier protein Scp2 (Krombach et al 2018 ); and (6) high-affinity sucrose transporter required for virulence Srt1 (Wahl et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is genomic evidence that some saprobic ustilaginalean yeasts, e.g. M.antarcticus , Kalmanozymabrasiliensis (= P.brasiliensis ), Pseudozymahubeiensis , and the yeast stage of M.bullatus (= P.aphidis ), have retained the capacity to produce effector proteins, which hints at the possibility that undiscovered plant pathogenic stages may exist for these fungi (Sharma et al 2018). Indeed, a teleomorph for M.antarcticus (= P.antarctica ) was recently reported for the first time on Echinochloacrus-galli (Tanaka et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Anthracocystis flocculosa (previously Pseudozyma flocculosa) genome contains a similar number of repeats (13.9%) and predicted effector genes (554, strict method) as the smut species U. hordei (16.5%) and U. maydis (553, strict method), respectively (30). Furthermore, the A. flocculosa genome is also compartmentalized with 54 predicted effectors residing in gene clusters, which are fewer genes than U. maydis (101) but more than U. hordei, which has none (30). In general, genes encoding for the secretome of Pseudozyma species strongly correspond with that of pathogenic smut species (97).…”
Section: Genome Evolution and Its Driversmentioning
confidence: 99%
“…Furthermore, Moesziomyces antarcticus still contains 21 of the 24 identified core effector candidates of smut pathogens, which caused Schuster et al (97) to hypothesize that M. antarcticus may still have the ability to infect plants. Comparative genome analysis performed by Sharma et al (101) has shown that 113 of a core set of 211 putative effector proteins were conserved among all pathogenic smut species and four tested Pseudozyma genomes. Furthermore, they also showed that U. maydis Pep1 homologs from the supposedly nonpathogenic yeasts are fully functional in U. maydis (101).…”
Section: Genome Evolution and Its Driversmentioning
confidence: 99%
See 1 more Smart Citation